Natural Pandemics during the Marinid Rule 668-869 AH / 1269-1465 in Fez: A Historical Study - AlQaisy, Mohammed (Al-Adab Journal, 2023)
During the Marinid rule, Morocco was important field of Islamic history. Fez was an important city in this country and became its capital during the Marinid rule. Natural phenomena in various aspects occurred in this city that left behind important effects such as starvation and drought, the destruction of people and animals, the demolition of houses, shops and public facilities like barrages as a result of floods or epidemics, and the destruction of crops due to the loss of rain or locusts. The study deals with the natural phenomena and the aspects related to them. The research includes a preface about the pandemic and its types with seven axes: winds and storms, drought or floods, eclipses, earthquakes, epidemics and diseases and locusts. All these phenomena and pandemics cause death or hunger to the human or the animal. The study includes the results related to this phenomena. The aim of the study is to know the natural phenomena that occurred, their causes and effects and the treatments taken to reduce them according to the scientific historical research by describing and analyzing the events and facts and connecting them scientifically.